Komparasi Kinerja Algoritma BFS, Dijkstra, Greedy BFS, dan A* dalam Melakukan Pathfinding - Nadila Sugianti; Ainatul Mardhiyah; Nurma Romihim Fadilah (JISKA (Jurnal Informatika Sunan Kalijaga), 2020)
Pathfinding is a computational process in finding the best route between two points or nodes to find the shortest path. This method has many algorithms that can be applied in various fields. In carrying out the pathfinding, speed and distance are considered as important. Through the test diagram, this paper illustrates the execution steps related to the pathfinding algorithm which includes BFS, Dijkstra, Greedy BFS, and A * for comparison. From several studies, the authors identified that execution time and mileage can be used optimally in the comparison process. Input variables as well as media used are 2-dimensional grids and heuristic function calculations. The analogy is carried out on a unity platform with the C# programming language, producing A * as a more flexible pathfinding algorithm to be implemented in various domains.